Longitudinal analysis of virtual community perceptions of cohesion: The role of cooperation, communication, and competition. (November 2018) - Lyles, Annmarie A; Loomis, Colleen; Mama, Scherezade K; Siddiqi, Sameer; Lee, Rebecca E
Online, virtual group interactions may help adherence to health promotion programs. The purpose of this study was to explore longitudinal relationships among dimensions of group cohesion and group-interaction variables to inform and improve group-based strategies within programs aimed at promoting physical activity in virtual communities. In all, 56 online virtual users completed a group dynamics–based physical activity promotion intervention and assessments of group cohesion and group interaction at baseline and 4 weeks. Friendly competition and cooperation were consistently strong predictors of cohesion. Facilitating a sense of friendly competition and cooperation may increase engagement in physical activity programs by bolstering group cohesion.